A organização textual do gênero artigo de opinião: uma abordagem à luz da teoria da estrutura retórica e da teoria das sequências textuais - Maria Risolina de Fatima Ribeiro Correia (2018)
This thesis presents a study of opinion articles from a social interactionist perspective of language, with the intention of identifying the text organization of this genre. The theoretical framework that supports this work is based, on the one hand, on functionalist studies, specifically, on the Rhetorical Structure Theory (RST), proposed by Mann and Thompson (1988). Focusing on consistency, the RST aims at text description, through the identification of the rhetorical relations which emerge between text spans, in order to verify their form of organization. The analyst processes the rhetorical relations identified, guided by the criterion of plausibility, so that a function is attributed to each information unit, according to what he or she judges to be most plausible. Text Linguistics is the other theoretical framework which supports the analysis undertaken here, especially Text Sequences Theory, as proposed by Adam (2011). This theory claims the compositional identification of text, with a look towards its linearity. The concepts of text and text genre were built upon Bakthin (1979), Beaugrande (1997), Depends (2002-2008), Bernárdez (1995), Costa Val (1999), Kock (2010), Antunes (2010). Argumentation was considered in the light of the studies by Chaim Perelman and Olbrechts-Tyteca (2005) in order to analyse the argumentative process materialized in the text. The hypothesis that we have raised is based on the fact that, to write an opinion article, the producer considers its communicative intent and makes choices which evidence the occurrence of certain rhetorical relations, such as elaboration, list, sequence, evidence and evaluation, as well as the predominance of argumentative sequences, thus resulting in the prototypicality of this genre. To that end, six of the twelve articles analyzed are presented; their selection is based on the criteria we have established. Among those, we have prioritized texts which exhibit the discussion of current topics considered relevant to the readers, on diverse themes and of different authors, published within the period of 2015-2016, in two weekly magazines - Carta Capital and Veja. Considering the text macro-structure, the analysis of articles presented us with rhetorical relations of the nucleus-satellite type, of the presentational kind, of attribution, enablement, preparation, evidence, justify and antithesis; of the hypotactic kind, the nucleus-satellite relations of evaluation, conclusion, elaboration, result and comment; of the paratactic kind, we have found the multinuclear relations of list and of sequence. We have verified, by means of the Text Sequences Theory, the predominance of argumentative sequences, followed by the descriptive and narrative sequences. The comparison of the results of the analysis of the two theories has confirmed a convergence between the theories, insofar as, in establishing a relation between the rhetorical structure - resulting from the macro-structure, verified through the RST and through the text plans of the six articles, built upon the text sequences - the prototypical organization of the genre opinion article was configured.